Kecerdasan Kinestetik Dalam Perspektif Islam - Syukur, Agus; Puspita, Ratna (Universitas Muhammadiyah Tangerang, 2024)
This research is driven by multiple factors, including the presence of a societal belief that students' intelligence can only be measured in specific subjects and accomplishments, despite the fact that intelligence is diverse. Additionally, there is an imbalance in assessing the three domains of cognition, emotion, and physical movement. Therefore, it is recommended to use authentic assessment as a balanced approach to evaluating learning in these domains. Furthermore, there is a lack of awareness within the Muslim community about the importance of physical movement intelligence, which actually aligns with the Prophet's teachings. The objective of this research is to raise awareness among the public and the education community that kinesthetic intelligence is a fundamental aspect of human intelligence. Developing this intelligence can lead to the acquisition of strong physical skills. It is important for the Muslim community to recognize the value of physical intelligence from an Islamic perspective, as advised by the Prophet. This research is qualitative in nature and adopts a descriptive approach. The findings indicate that kinesthetic intelligence can enhance students' psychomotor abilities, improve social interactions, and promote physical well-being. Individuals with kinesthetic intelligence can pursue further education and careers in fields that align with their intelligence, such as athletics, choreography, acting, and modeling. Teaching methods that can be employed to develop this intelligence include demonstrations, theater classes, and role-playing.